Proposal for improving white-space channel availability - Aji, L.; Juwono, Filbert Hilman; Wibisono, G.; Gunawan, D. (IEEE Access, 2018)
© 2018 IEEE. A major concern in implementing white-space technology in a television broadcasting system is the ability of the system to provide information about the vacant channels while guaranteeing protection to its primary users. Moreover, in the developing countries, the allocation of television broadcasting channels is not as good as that in the developed countries. Therefore, there is a high possibility of overlaps between the digital television terrestrial coverage areas and white-space areas. Herein, we propose a method involving the use of four zones-prohibited, strict, moderate, and loose (PSML)-to model the television white-space system. We use a television coverage area that has less than 70% location probability to accommodate the possibility of overlaps between the white space and the protection areas. We also propose a protection ratio value to complement the standard given by the Federal Communications Committee (FCC) for countries implementing the digital video broadcasting system (DVB-T2). We conduct a test to analyze the implementation of the proposed PSML method in Bali Island, Indonesia. The results show that our model can provide more white-space channels than the models proposed by Villardi and the FCC when applied to transition areas between urban and rural regions.